Impact of COVID-19 on Quality of Life of Medical Students and its Relationship with Resilience - Parajuli, Sudhir Raman; Manandhar, Varsha (Nepal Journal of Medical Sciences, 2024)
Introduction: Quality of life (QoL) is a concept designed to measure the overall well-being of an individual or population, encompassing both positive and negative aspects of their existence at a particular moment in time. Various stressors impact quality, and any unforeseen pandemic can alter this among medical students too. Resilience is an individual capacity to bounce back from this type of event. This study tries to find the impact of COVID-19 among medical students regarding quality of life and their resilience. Methods: All 379 consenting medical students of Manipal College of Medical Sciences were included in the study. QoL was measured using the World Health Organization Quality of Life - BREF (WHOQOL-BREF) questionnaire, and resilience was measured by Connor-Davidson Resilience Scale 10 Item (CD-RISC-10). SPSS ver. 16.0 was used for calculation of descriptive statistics and to find the association between dependent and independent variables. Results: The total score for quality of life ranged from 47 to 125 with the mean and standard deviation score being 90.56 ± 13.70. Among the individual domains, physical domain had the highest mean score of 65.42 ± 15.207, while psychological domain had the lowest mean score of 59.34 ± 16.92. Self-reported mean resilience score was 25.81 ± 6.66. Conclusions: Physical domain of QoL was found to be significantly high in medical students even during COVID-19 whereas psychological domain was low. Resilience has a significant impact on students' QoL, and thus higher resilience improves QoL.